PEMANFAATAN KALAMBUAI (POMACEA CANALICULATA) SEBAGAI SUMBER PROTEIN DALAM PRODUKSI RANSUM TRADISIONAL ITIK PEKING (ANAS PLATYRHYNCHOS DOMESTICUS): UTILIZATION OF KALAMBUAI POMACEA CANALICULATA)AS A SOURCE OF PROTEIN IN TRADITIONAL RATION PRODUCTION OF PEKING DUCKS (ANAS PLATYRHYNCHOS DOMESTICUS) - Ulumuddin, Ihya; M Istyadji; E Hafizah (Jurnal Peternakan Nusantara, 2023)
Making traditional poultry rations using kalambuai is one of the local wisdoms. This research is a study on the utilization of kalambuai (Pomacea canaliculata) as a source of protein in the manufacture of traditional rations in accelerating the growth and development of Peking ducks (Anas platyrhynchos domesticus). The purpose of this study was to determine the nutritional content in the kalambuai ration and its effect on the growth and development of Peking ducks. Homemade rations were able to achieve better results than feed from factories. The type/research model used in this study used a completely randomized design experimental research model. The data collection technique used is direct observation and experimentation techniques. All data obtained from the results of the study were analyzed by analysis of variance based on a one-way completely randomized design (CRD) to determine the effect of treatment on the observed modifiers. The results of this study concluded in the form of (1) The protein content of the feed made from calambuai was around 18.2 and 17.5, (2) The ducks that had the best growth were the ducks that were given kalambuai feed, then br-1 comfeed, and the most only bran is bad, (3) In terms of body weight growth and economy, kalambuai feed is better than comfeed br-1 feed.